WOMEN FEEL MORE PESSIMISTIC THAN MEN: EMPIRICAL EVIDENCE FROM TURKISH CONSUMER CONFIDENCE INDEX - ÇELİK, SADULLAH (VILNIUS GEDIMINAS TECH UNIV, 2010)
The leading role that is attributable to economic indicators like consumer confidence has been well documented in the literature for many developed nations. Moreover, the relationship between high frequency financial market data has been a common research topic for world economies. However, there is hardly any study that attempts to search for the possible functional relationship between consumer confidence and financial market variables. This paper is a simple attempt to link these two brands of literature by focusing on the relationship between financial market variables and consumer confidence index before the global crisis has started. We have two distinctive points. First, we derive separate consumer confidence indices for men and women by employing micro-level consumer confidence data from an emerging market (Turkish CNBC-e consumer confidence index) for the period of January 2003 - January 2008. Second, employing this data set, we do not only check for the existence of a relationship between consumer confidence and financial market variables (such as interest rates, exchange rates and stock exchange index) but also focus on the possibility of gender response. We find evidence of gender response difference as throughout the period women are more pessimistic than men-due probably to lower levels of wealth-and respond less to changes in exchange rates than men-due probably to lower purchasing power.
Keywords: consumer confidence; emerging market; financial market variables; gender response; co-integration; AUTOREGRESSIVE TIME-SERIES; FINANCIAL DECISION-MAKING; EXCHANGE-RATE; STOCK-MARKET; UNIT-ROOT; GENDER-DIFFERENCES; COINTEGRATION; SENTIMENT; BEHAVIOR; MODELS